Phytochemical and Insecticidal Screening of The Leaf Extract of Heliotropium indicum L. - Dolui, A.K.; Debnath, M.; De, B. (Asian Journal of Chemistry, 2010)
The leaves of Heliotropium indicum was extracted with petroleum ether, ethyl acetate and methanol. Different concentrations were made from each crude extract and applied for insecticidal activity (antifeedant activity) against Helopeltis theivora. Out of all the extracts methanolic extract has shown highest activity. Fractionation of effective crude extracts (methanolic extract) by column chromatography revealed that the fraction No. V is most toxic against the pest. Qualitative phytochemical analysis of most effective crude extract has also been performed.